Effects of isolation condition and spray drying on camelina gum yield and properties - Cao, Xiwen (Kansas State University, 2017)
Camelina sativa (L). Crantz that belongs to Brassicaceae family has been grown as a dicotyledonous oilseed crop in the cold places like America and Canada. Camelina seeds are widely used for the extraction of oil and protein. Recently, research found that camelina gum is an excellent candidate for food and industrial uses as thickener or stabilizer. The objectives of this research were 1) to increase camelina gum isolation efficiency using spray drying technology, and 2) to develop an innovative method to remove gum from seed bran to increase protein and oil extraction efficiency and quality. The camelina gums isolated using ethanol precipitation and spray drying method from the whole camelina seeds were compared. Effects of spray drying temperature on yield, gum morphology, and gum rheological and thermal properties were studied. The representative sample dried at 165°C was chosen to study the effects of concentration, temperature, pH and additives (NaCl, CaCl₂, sucrose, and ethanol) on viscosity and viscoelastic properties of the isolated gum. The gum showed a shear thinning behavior when shear rate increased gradually, higher concentrations of additives only slightly affect the rheological properties. Results showed that spray drying is an effective method in terms of saving time and energy, and provided positive rheology benefits on camelina gum isolation. Pre-removal of gum from camelina seeds can increase protein and oil yield and their quality. Decortication can separate 10-17% of the total camelina seed as bran. A wind tunnel was used to separate lighter bran particles from heavier endosperm and unbroken seeds. Camelina gum isolation from the separated seed bran using the traditional ethanol precipitation method was optimized using response surface methodology where the simultaneous effect of the three independent variables (seed bran to water ratio, isolation temperature, and isolation time) were investigated for gum yield, purity, and optimum rheological properties. Three independent quadratic modules were developed and the original data fitted the models fitted (R² = 0.995, 0.877, and 0.804). The optimal isolation conditions were seed bran to water ratio of 1:39, isolation temperature of 35 ºC, and isolation time of 1.5 h and 0.839 desirability was obtained by the rigorous statistics analysis. The protein yield and quality extracted from decorticated endosperm were improved significantly compared with that extracted from whole seeds meal without decortication. In addition, the degumming step can be eliminated before protein and oil extraction that increase protein and oil extraction efficiency.
Keywords: Camelina Sativa; Bran decortication; Response surface methodology; Spray dry; Rheological property